2015
DOI: 10.1007/s12630-015-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pneumoperitoneum and Trendelenburg positioning on respiratory system mechanics during laparoscopic pelvic surgery in children: a prospective observational study

Abstract: Purpose The aim of this study was to describe the changes in respiratory system compliance and other measures of respiratory mechanics associated with peritoneal insufflation (12 mmHg pressure) with carbon dioxide (PNP12) and 20°Trendelenburg positioning (TDG20) in pediatric patients undergoing laparoscopic surgery for abdominal cryptorchidism.Methods Twelve subjects with abdominal cryptorchidism undergoing orchiopexy were enrolled in the study. General anesthesia was conducted with sevoflurane/O 2 /air, fenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In our study, under the condition of unchanged PEEP, C RS and C lung decreased during pneumoperitoneum as was expected [14,15]; however, in contrast to our hypothesis, compliance did not fully recover after removal of the pneumoperitoneum. Closely related, the analysis of the intratidal compliance profiles revealed an increase in intratidal recruitment/derecruitment during and only a partial recovery after removal of the pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 58%
“…In our study, under the condition of unchanged PEEP, C RS and C lung decreased during pneumoperitoneum as was expected [14,15]; however, in contrast to our hypothesis, compliance did not fully recover after removal of the pneumoperitoneum. Closely related, the analysis of the intratidal compliance profiles revealed an increase in intratidal recruitment/derecruitment during and only a partial recovery after removal of the pneumoperitoneum.…”
Section: Discussionsupporting
confidence: 58%
“…Spadaro et al have investigated the effect of three different levels of PEEP (0, 5, and 10 cmH 2 O) in adult patients undergoing either laparotomy or laparoscopic surgeries using intraoperative shunt levels and dynamic compliance as assessment parameters . They concluded that a more aggressive PEEP level is required to reduce shunt and to normalize respiratory compliance during laparoscopic surgery because of the reduction of FRC caused by the pneumoperitoneum . Acosta et al suggested that PEEP levels higher than the usual 5 cmH 2 O would be required to preserve normal lung aeration during pneumoperitoneum in pediatric laparoscopic surgeries .…”
Section: Discussionmentioning
confidence: 99%
“…Atelectasis and poorly ventilated lung areas are negative consequences of general anesthesia observed in adults as well as in children secondary to the reduction of the end‐expiratory lung volume (FRC) and the resultant airway closure, consequently leading to decreased lung compliance, impairment of oxygenation, increased pulmonary vascular resistance, and development of lung injury . Laparoscopic surgery with associated pneumoperitoneum further worsens respiratory mechanics accentuating atelectasis formation . Studies show a strong correlation between the development of atelectasis and postoperative pulmonary complications (PPCs)…”
Section: Introductionmentioning
confidence: 99%
“…The single incision laparoscopy needs sufficient operating room inner the abdomen; thus, the high pressure of pneumoperitoneum might affect the respiratory system. [29,30] For an enhanced cosmetic look of the 2-port laparoscopy, the infra-umbilical incision and 3 mm scars near the umbilical were made nearly invisible with the help of topical skin adhesive to avoid suturing.…”
Section: Discussionmentioning
confidence: 99%